Building on 150 Years of Knowledge: The Freshwater Isopod Asellus aquaticus as an Integrative Eco-Evolutionary Model System - Lafuente, Elvira; Lürig, Moritz D.; Rövekamp, Moritz; Matthews, Blake; Buser, Claudia; Vorburger, Christoph; Räsänen, Katja (Frontiers in Ecology and Evolution, 2021)
Interactions between organisms and their environments are central to how biological diversity arises and how natural populations and ecosystems respond to environmental change. These interactions involve processes by which phenotypes are affected by or respond to external conditions (e.g. via phenotypic plasticity or natural selection) as well as processes by which organisms reciprocally interact with the environment (e.g. via eco evolutionary feedbacks). Organism-environment interactions can be highly dynamic and operate on different hierarchical levels, from genes and phenotypes to populations, communities, and ecosystems. Therefore, the study of organism-environment interactions requires integrative approaches and model systems that are suitable for studies across different hierarchical levels. Here, we propose the freshwater isopod Asellus aquaticus, a keystone species and an emerging invertebrate model system, as a prime candidate to address fundamental questions in ecology and evolution, and the interfaces therein. We review major fields of research that have used A. aquaticus and draft a set of specific scientific questions that are well suited to be answered using this species. Specifically, we propose that A. aquaticus can aid in understanding i) the influence of host-microbiome interactions on organismal and ecosystem function, ii) the relevance of biotic interactions in ecosystem processes, and iii) how ecological conditions and evolutionary forces lead to phenotypic diversification.